1998
DOI: 10.1103/physrevstab.1.053501
|View full text |Cite
|
Sign up to set email alerts
|

Hcharge-exchange injection without hazardous stripping foils

Abstract: A new scheme of H 2 charge-exchange injection without stripping foils is proposed. It is composed of a neutralizer of the H 2 beam using Lorentz stripping, the colliding system of a high power laser and the H 0 beam to excite H 0 atoms to the 3P state using the Rabi oscillation, and a magnet to strip the H 0 ͑3P͒ to a proton beam by Lorentz stripping. The necessary laser wavelength, laser power, magneticfield gradient, and maximum magnetic field are estimated for a beam energy from 1.0 to 3.0 GeV. The result s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…While in theory it is possible to remove the second electron using direct laser photo-detachment, it would require excessively high peak laser powers. Instead, a laser is used to produce resonant excitation of the remaining electron to a higher quantum state (H 0 *) with lower binding energy [5], and then it is Lorentz stripped by a second dipole magnet to produce a proton (H 0 * to p). The process is shown schematically in Fig.…”
mentioning
confidence: 99%
“…While in theory it is possible to remove the second electron using direct laser photo-detachment, it would require excessively high peak laser powers. Instead, a laser is used to produce resonant excitation of the remaining electron to a higher quantum state (H 0 *) with lower binding energy [5], and then it is Lorentz stripped by a second dipole magnet to produce a proton (H 0 * to p). The process is shown schematically in Fig.…”
mentioning
confidence: 99%
“…At present, the possibility of laser assisted charge exchange injection of a high-energy hydrogen beam with the help of powerful laser and magnetic fields is widely discussed [1][2][3][4][5][6][7]. A wide review on laser stripping and its achievements can be found in [2,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…For calculations and measurements of Lorentz stripping of H -s see refs [6][7][8] and [1]. Further relevant references are given in ref [4].…”
Section: H -Strippingmentioning
confidence: 99%
“…Because of space limitations we restrict to comments on the main components and critical parts of Lolas schemes, for which refs [1][2][3][4][5] give extended sets of references and the essential formulas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation